Sikap Boros: Dari Normatif Teks ke Praktik Keluarga Muslim - Murtadho Ridwan; Irsad Andriyanto (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2019)
AbstractThis study aims to describe wasteful behaviour in terms of normative texts, Islamic economics, and practices in Muslim families. The approach used is a descriptive approach by describing the wastefulbehaviour of the Qur'an and Hadith arguments and mentioning the opinion of Islamic economists. This study is complemented by a survey of 25 Muslim families to find wasteful out their level of consumption in the month of Ramadan. The results of the study show that is explained in the Qur'an and hadith with two terms, those are israf and tabdzir. Islam prohibits wasteful in consumption, but wasteful limitations in Islamic economics are relative (subjective). While the survey results concluded that the majority of Muslim family consumption in the month of Ramadan increased. The increasing aims to meet the needs of four healthy five perfect. The food provided by Muslim families in the month of Ramadan is in accordance with the needs so that nothing is wasted. For those who have leftovers, they use of it for pets so it does not include wasteful. There was only one respondent who claimed to throw away leftovers in vain so that the wasteful behaviour was prohibited by Islam.Keywords:Wasteful, Consumption Ethics, Islamic Economy AbstrakKajian ini bertujuan untuk mendiskripsikan sikap boros dari segi normative teks, ekonomi Islam, dan praktik di keluarga Muslim. Pendekatan yang digunakan adalah pendekatan deskriptif dengan mendiskripksian sikap boros dari dalil Alquran dan Hadis serta menyebutkan pendapat ahli ekonomi Islam. Kajian ini dilengkapi dengan hasil survey kepada 25 keluarga Muslim untuk mengetahui tingkat konsumsi harian mereka di bulan Ramadhan. Hasil kajian menunjukkan bahwa sikap boros dijelaskan dalam Alquran dan hadis dengan dua istilah, yaitu israf dan tabdzir. Islam melarang sikap boros dalam berkonsumsi, namun batasan boros dalam ekonomi Islam bersifat nisbi (subyektif). Sedangkan hasil survey menyimpulkan bahwa mayoritas konsumsi harian keluarga Muslim di bulan Ramadhan mengalami peningkatan. Peningkatan tersebut bertujuan untuk memenuhi kebutuhan empat sehat lima sempurna. Makanan yang disediakan keluarga Muslim di bulan Ramadhan sesuai dengan kebutuhan sehingga tidak ada yang terbuang sia-sia. Bagi yang memiliki sisa makanan, mereka memanfaatkan untuk hewan peliharaan sehingga tidak termasuk sikap boros. Hanya ada satu responden yang mengaku membuang sisa makanan dengan sia-sia sehingga perilaku itu termasuk boros yang dilarang Islam.Kata kunci: Boros, Etika Konsumsi, Ekonomi Islam